2018
DOI: 10.3390/cosmetics5040059
|View full text |Cite
|
Sign up to set email alerts
|

Formulating O/W Emulsions with Plant-Based Actives: A Stability Challenge for an Effective Product

Abstract: Quality, safety, and efficacy concerns added to instability, poor absorption, and the dispersion of actives are common problems while formulating plant-based cosmetics. Furthermore, a correct balance between the stability of the emulsion, the sensory profile, and the high efficacy has to be considered to formulate an effective product. In this paper, we demonstrate that rheology is a methodological tool that can be used while designing a new product. In particular, we developed an O/W emulsion which is easy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
(15 reference statements)
0
21
0
2
Order By: Relevance
“…Defects in the viscosity of the final formulations would potentially provoke phase separation and liquefaction. For the improvement of the long term stability of the prepared emulsions as well as the increase of their viscosity during storage, the addition of acrylic polymers in the aqueous phase of O/W emulsions has been proposed [ 76 ]. Furthermore, it was found that the addition of various nanoparticles during storage results in an augmentation of the emulsion’s viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Defects in the viscosity of the final formulations would potentially provoke phase separation and liquefaction. For the improvement of the long term stability of the prepared emulsions as well as the increase of their viscosity during storage, the addition of acrylic polymers in the aqueous phase of O/W emulsions has been proposed [ 76 ]. Furthermore, it was found that the addition of various nanoparticles during storage results in an augmentation of the emulsion’s viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Producers are widening their palette of natural cosmetics to ride the trend of changing consumer attitude [40]. The science of rheology is an efficient tool of cosmetic products, which includes green cosmetics activities, the supply of consumer demands, and the stability of the product ( Figure 2) [41]. The original factors of rheology as a powerful tool for cosmetic product design, we have been supplemented based on our analyses.…”
Section: Responsibility Of Cosmetics Producersmentioning
confidence: 99%
“…The main source of extracting bio-active natural ingredients are plants, most notably herbs and spices [46]. Plant-based active ingredients usable in both traditional pharmaceutical products and functional cosmetics for a longer period, can be applied to the current trend of the green cosmetics market with their well-documented biological effects [41].…”
Section: Responsibility Of Cosmetics Producersmentioning
confidence: 99%
See 1 more Smart Citation
“…It also seemed likely that the colour changes of Kyoho skin emulsions were due to Kyoho skin and extracts that probably changed the colour of the formulated emulsion. These findings agreed with those of earlier studies (Khan et al ., 2010; Semenzato et al ., 2018), who observed the addition of plant extracts resulted in changes to structure and visual colour of emulsions.…”
Section: Resultsmentioning
confidence: 99%